Accounting for taste: An examination of socioeconomic gradients in attendance at arts events - Pete Lunn; Elish Kelly (The Economic and Social Research Institute (ESRI), 2009)
We critically examine and empirically test the hypothesis that the strong socioeconomic gradients characterising attendance at arts events result from similar gradients in preferences for the arts, in line with existing theories of demand for the arts derived from orthodox consumer theory. To control for preferences, we use individual measures of stated interest in the arts and reports of viewing and listening habits, as distinct from attendance at live events. These variables are strongly associated with attendance, yet despite their inclusion as covariates within a hierarchical logistic regression analysis, strong and significant socioeconomic gradients remain within the estimated models. While it remains possible that our controls do not capture sufficient variation in preferences for the arts, it appears more likely that the socioeconomic composition of live arts audiences is influenced by other factors in addition to individual preferences for the arts.
Keywords: Z11; 330; arts participation; socioeconomic gradients; logistic regression; Ireland; Kultursektor; Konsumentenverhalten; Offenbarte Präferenzen; Regression; Irland